Import control under regionalism in colonial Nigeria, 1954-1960 (2019)
The colonization of Nigeria by the British opened a new vista in the history of the country as various ethnic groups came under the British system of administration. Parts of the colonial administrative structures included, native courts, native authorities, native treasuries and protectorates. Historians, political scientists, sociologists, economists and scholars of various disciplines have through their works, interrogated Nigeria’s colonial past. Indirect rule system, colonial infrastructure, the rise of nationalism, currency circulation, colonial system of banking, colonial system of education and exploitation of Nigeria’s resources are typical examples of Nigeria’s colonial experience. Similarly, scholars have made attempts at interrogating various aspects of the country’s colonial history. These include, colonial agricultural policies, colonial export control policies, marketing boards, trade restrictions, politics of decolonization, politics of transfer of power, constitutional developments, regionalism, nationalist movements, colonial tariff system and issues that deal with Nigeria’s economic development in the colonial period. These intellectual efforts have not beamed their searchlight on how import control in an era of regionalism was used as one of the strategies of decolonization before the country’s independence. Thus, the interrogation of a history of import control as an integral part of decolonization seems to have been neglected. It is against this backdrop that this paper interrogated import control as colonial economic policy which aided the entrenchment of regionalism in Nigeria. The paper in its conclusion argued that import control under regionalism was one of the strategies used by the colonial government in the devolution of some of its economic powers to the regions through constitutional framework.